Evaluation of Temper Embrittlement of 30Cr2MoV Rotor Steels Using Electrochemical Impedance Spectroscopy Technique - Zhang Shenghan; Lv Yaling; Tan Yu (Journal of Spectroscopy)
Temper embrittlement tends to occur in the turbine rotor after long running, which refers to the decrease in notch toughness of alloy steels in a certain temperature range (e.g., 400°C to 600°C). The severity of temper embrittlement must be monitored timely to avoid further damagement, and the fracture appearance transition temperature (FATT50) is commonly used as an indicator parameter to characterize the temper embrittlement. Compared with conventional destructive methods (e.g., small punch test), nondestructive approaches have drawn significant attention in predicting the material degradation in turbine rotor steels without impairing the integrity of the components. In this paper, laboratory experiments were carried out based on a nondestructive method, electrochemical impedance spectroscopy (EIS), with groups of lab-charged specimens for predicting the temper embrittlement (FATT50) of turbine rotor steel. The results show that there was a linear relationship of interfacial impedance of the specimens and their FATT50 values. The predictive error based on the experiment study is within the range of ±15°C, indicating the predicting model is precise, effective, and reasonable.